Poetic Imagination: Love and Longing among Syrian Men in Exile in Amman. Issue 2 (1st December 2021) - Mortensen, Emilie Lund
Abstract: In this article, I attend to poetic expressions of passionate longing for a beloved among displaced single Syrian men in the Jordanian capital of Amman. With a point of departure in the story and poetry of Qays, a 28-year-old Syrian man from Damascus, the article engages in an exploration of the poetic space engendered in the process of writing and reading poetry in exile. It demonstrates how longing found expression and relief in love poetry, as it enabled the young Syrian men to, momentarily, displace themselves to a different time and place, closer to the women they longed for. The poetry I thus argue, engenders and constitutes a creative space of possibility in which the impossible becomes possible in exile.